Variasi Lingkungan Perairan dan Respons Komunitas Lamun di Pulau Pahawang - Lestari, Tridyah; Aryawati, Riris; Aryawati, Wike Ayu Eka; Melki; Purwiyanto, Anna Ida Sunaryo (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
Seagrass ecosystems play a crucial role in maintaining coastal environmental stability, yet their presence in Pahawang Island shows a declining trend due to human activity pressures and changes in aquatic conditions. This study aims to describe the structure of the seagrass community and analyze its correlation with environmental parameters at four stations with different characteristics. Seagrass data collection was conducted using the transect-quadrant method to measure coverage, density, and species composition, while environmental parameters observed included temperature, salinity, pH, dissolved oxygen (DO), current, and water clarity. The results showed the presence of three seagrass species, namely Enhalus acoroides, Thalassia hemprichii, and Halodule uninervis, with varying coverage and density across locations; the best condition was found at the natural station and the lowest at the pier area. The diversity index was classified as low, while uniformity and dominance varied according to human activity levels around the water. PCA analysis indicated that salinity, current, clarity, DO, pH, and temperature contribute differently at each station and collectively influence the variation in the seagrass community. These findings emphasize that differences in environmental quality and the intensity of anthropogenic disturbances are key factors determining the condition of the seagrass beds in Pahawang Island. Keywords: Seagrass, Water Quality, Community Structure, PCA, Pahawang Island